Kemampuan Literasi Sains Siswa Sekolah Dasar dan Madrasah Ibtidaiyah Berdasarkan Gaya Belajar dan Gender - Safar, Nurbaya; Makian, Indri; Ningsi, Fitra; Nurjannah, Nurjannah; Ariflukmana, Dana (Peneliti.net, 2023)
Scientific literacy skills are not only about skills in reading and just understanding science, but also abilities that are able to apply the concept of scientific literacy knowledge in real life. Scientific literacy can be interpreted as a person's ability to understand science, communicate science and apply scientific knowledge to solve problems, so as to increase attitudes and sensitivity to the surrounding environment. There are several factors that can affect students' scientific literacy skills. These factors include: learning style and gender.